Efek Konsentrasi Eko-Enzim dan Pupuk NPK Terhadap Pertumbuhan Bibit Kopi Liberika (Coffea Liberica W Bull Ex Hiern) Tungkal Jambi - Sapitri, Giya Ayuni; Maryani, Anis Tatik; Swari, Elly Indra (Universitas Batanghari Jambi, 2024)
This study aims to investigate the influence of various concentrations of Eco-Enzyme and NPK fertilizer on the growth of Liberika Tungkal Jambi coffee seedlings and to determine the optimal concentrations of Eco-Enzyme and NPK fertilizer for the growth of Liberika Tungkal Jambi coffee seedlings. The study utilized a Randomized Block Design (RAK) consisting of 6 treatment levels, as follows: P0 = No Eco-Enzyme (100% Inorganic Fertilizer), P1 = Eco-Enzyme Concentration 50 mL. + 50% Inorganic Fertilizer, P2 = Eco-Enzyme Concentration 100 + 50% Inorganic Fertilizer, P3 = Eco-Enzyme Concentration 150 mL. + 50% Inorganic Fertilizer, P4 = Eco-Enzyme Concentration 200 mL. + 50% Inorganic Fertilizer, and P5 = Eco-Enzyme Concentration 250 mL.+ 50% Inorganic Fertilizer. The observed variables included plant height, number of leaves, stem diameter, total leaf area, shoot dry weight, root dry weight, and root shoot ratio.The research findings indicate that the application of Eco-Enzyme and NPK fertilizer had an impact on the growth of 6-month-old Liberika Tungkal Jambi coffee seedlings, particularly in terms of the number of leaves and total leaf area. The concentration of Eco-Enzyme at 50 mL.+ 50% Inorganic Fertilizer yielded the best growth results for the coffee plants.